The letters of Shirley Jackson - Jackson, Shirley, 1916-1965 (Random House, 2021)
"Shirley Jackson is one of the most important American authors of the last hundred years and among our greatest writers of the female experience. This extraordinary compilation of personal correspondence has all the hallmarks of Jackson's beloved fiction, and also features family photographs and Shirley's own illustrations. Written over the course of nearly three decades, from Jackson's college years to three months before her premature death at the age of forty-eight, these letters become the autobiography Shirley Jackson never wrote, full of subversive wit, vivid imagination, and gorgeous prose. Jackson spent much of her adult life as a faculty wife and mother of four in Vermont, and the landscape here is the everyday: trips to the dentist and dream vacations, overdue taxes and broken Christmas tree bulbs, new dogs and new babies, fad diets and recipes for fudge. But in recounting these events to family, friends, and colleagues, she turns them into remarkable stories: entertaining, revealing, and wise. This intimate collection holds the beguiling prism of Shirley Jackson--writer and teacher, mother and daughter, neighbor and wife--up to the light"--